Access to justice for people with disabilities in employment - Imam Wicaksono (Jurnal Hukum Volkgeist, 2019)
Access to Justice for people with disabilities is a term used to describe the legal protection given to persons with disabilities in their efforts to meet their needs from things that can endanger persons with disabilities themselves.The right to obtain employment including for workers with disabilities is regulated in the Indonesian state constitution. Therefore, these rights are protected and guaranteed by law, so companies that employ persons with disabilities in particular must protect the rights of persons with disabilities.The method used in this study is this research is a type of normative law research using normative legal case studies in the form of legal behavior products. Persons with disabilities must receive the support needed in the structure of education, health, employment and social services, so that the rights of persons with disabilities are in the perspective of human rights. Normatively, there are actually several legal instruments that have been born to protect the rights of persons with disabilities to work. Law No. 13 of 2003 concerning Employment which forbids discrimination to persons with disabilities The right of persons with disabilities to obtain accessibility contained in Article 18 of Law No.8 / 2016 concerning Persons with Disabilities, namely, obtaining accessibility to utilize public facilities and obtain adequate accommodation as a form of accessibility for individuals.